2018
DOI: 10.1130/g40224.1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-proxy record of the Chicxulub impact at the Cretaceous-Paleogene boundary from Gorgonilla Island, Colombia

Abstract: A 40 m stratigraphic section at Gorgonilla Island, Colombia, provides a unique deepmarine, low-latitude, Southern Hemisphere record of events related to the end-Cretaceous Chicxulub impact and the global Cretaceous/Paleogene boundary (KPB). The KPB is marked by a 20-mm-thick, densely packed spherule bed as defined by planktic foraminifera, in contrast to complex relationships found in high-energy, impact-proximal sites in the Gulf of Mexico and Caribbean basins. The absence of basal Danian foraminiferal Zone P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
6
23
1
Order By: Relevance
“…This recalculated age is within uncertainty indistinguishable from the more recent U-Pb age of 66.021 -0.081 Ma for zircon crystals in ash layers around the K/T boundary in the Denver Basin (Clyde et al, 2016). It is also equivalent to Ar-Ar results of 66.038 -0.049 Ma for glassy microtektites found at the K/T boundary in Beloc, Haiti (Renne et al, 2013;Sprain et al, 2015), an age of 66.051 -0.031 Ma for similar microtektites at a K/T section exposed on Gorgonilla Island off the coast of Colombia (Renne et al, 2018), and an age of 66.052 -0.043 Ma for tephra in the ''Iridium Z coal'' layer *1 cm above the iridium anomaly of the K/T boundary interval (Renne et al, 2013;Sprain et al, 2018). The *24 kmdiameter Boltysh impact structure in Ukraine, another end-Cretaceous impact structure (Kelley and Gurov, 2002), has a recalculated age of 65.80 -0.67 Ma that is, within a somewhat larger error envelope, identical to the age of the Chicxulub impact ( Jourdan, 2012).…”
Section: Ar-ar Agessupporting
confidence: 64%
See 2 more Smart Citations
“…This recalculated age is within uncertainty indistinguishable from the more recent U-Pb age of 66.021 -0.081 Ma for zircon crystals in ash layers around the K/T boundary in the Denver Basin (Clyde et al, 2016). It is also equivalent to Ar-Ar results of 66.038 -0.049 Ma for glassy microtektites found at the K/T boundary in Beloc, Haiti (Renne et al, 2013;Sprain et al, 2015), an age of 66.051 -0.031 Ma for similar microtektites at a K/T section exposed on Gorgonilla Island off the coast of Colombia (Renne et al, 2018), and an age of 66.052 -0.043 Ma for tephra in the ''Iridium Z coal'' layer *1 cm above the iridium anomaly of the K/T boundary interval (Renne et al, 2013;Sprain et al, 2018). The *24 kmdiameter Boltysh impact structure in Ukraine, another end-Cretaceous impact structure (Kelley and Gurov, 2002), has a recalculated age of 65.80 -0.67 Ma that is, within a somewhat larger error envelope, identical to the age of the Chicxulub impact ( Jourdan, 2012).…”
Section: Ar-ar Agessupporting
confidence: 64%
“…They are, moreover, characterized by their internal statistics expressed through MSWD and p values for plateau sections and isochrons (and are typically reported with 2s errors; that is, at the *95% confidence level, as is done in this work unless otherwise stated). Precise Ar-Ar ages have been obtained for a number of impacts on Earth, such as 66.052 -0.031 Ma for glassy microtektites from the 180 km-diameter Chicxulub crater linked to the end-Cretaceous mass extinction (Renne et al, 2018). High-precision Ar-Ar results for the Chicxulub microtektites at the K/T boundary (more recently also known as the K/Pg boundary) were recently used to calibrate the timing and duration of the contemporaneous reverse magnetic chron C29r (Sprain, 2017;Sprain et al, 2018).…”
Section: Ar-ar Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…These impact deposits, which formally were deposited within the Cenozoic (Danian) (26), thicken and becomes more stratigraphically complex with proximity to the crater (25). K-Pg boundary sections around coastal and shelf sites in the Gulf of Mexico and Caribbean show a mixture of material delivered by airfall, shelf collapse, debris flows, and tsunami (27)(28)(29)(30)(31)(32). Within the deep water Gulf of Mexico, earthquake energy from the impact triggered gravity flows on continental slopes, generating the largest known event deposit on Earth (33).…”
Section: Significancementioning
confidence: 99%
“…. 2004,2007, for mature forms of that position), accurate 40 Ar/ 39 Ar dating of impact glass within the K-Pg layer (Renne et al, 2013(Renne et al, , 2018, as well as dating of microcrystalline melt rock (Swisher et al, 1992) and shocked zircon (Krogh et al, 1993;Kamo et al, 2011) from Chicxulub and the K-Pg layer, clearly demonstrate that Chicxulub is the site of the K-Pg impact. Hildebrand et al (1991) also noted that Gulf of Mexico DSDP Sites 94, 95, 536, and 540 contained deepwater gravity flows and turbidity-current deposits adjacent to Campeche Bank, and DSDP Sites 603B, 151, and 153, as well as outcrops along the Brazos River in Texas, contained potential tsunami wave deposits (Bourgeois et al, 1988), all of which suggested these deposits were a result of the Chicxulub impact.…”
mentioning
confidence: 89%